Advancing Artificial Intelligence in Criminal Investigation: AComprehensive Review and Future Directions - Aditya Kumar; Vinny Sharma; Sudhir Kumar; Arvind Kumar (Indian Journal of Forensic Medicine and Pathology, 2025)
The willingness enables an electronic device or technology to accomplish projects that a human can do but faster and with fewer errors, like speech recognition, visual perception, cognitive thinking, decision-making, and experiential education, it is known as machine learning or Arti𿿿cial Intelligence (AI). The many recent areaof development that is utilized to improve the application of arti𿿿cial intelligence(AI) in the domains of scienti𿿿c investigation and the judicial system. Experts inScience of Crime and criminal investigation face many challenges today, including the deluge of data, the minute elements of testimony in the complex and chaotic conditions, the usual scienti𿿿c setups, and occasionally the ignorance that couldlead to a miscarriage of justice or an unsuccessful investigation. AI is the weapon of choice for overcoming various deep learning and machine learning-related problems. And to achieve such without error, impartial, and repeatable leads to in numerous forensics𿿿elds, neural networks have produced and ase-based easoning are utilized. These days, arti𿿿cial intelligence (AI) is helping ractically very well-known𿿿eld in forensic science and criminal investigation. It does this rough a variety of methods that include data extraction, statistical evaluation and probable techniques, machine learning, detection of patterns, image processing, machine learning, analysis of information, analytical and numerical methods, and pictorial modelling. Arti𿿿cial intelligence is assisting frensic ecialists and investigators by creating rational proof, creating three-dimensional reconstructions of scene of crime, ef𿿿ciently managing evidence, and asessing i to draw reasonable inferences at different stages of an examination. In addition to